PRINSIP-PRINSIP KASIH SESAMA PESERTA DIDIK BERDASARKAN ROMA 12:9-10 DI SDN 008 SAMARINDA ULU - Titin Herlina; Tabita Tandian (Metanoia, 2022)
There are many students who have good abilities in learning and achievement at school but do not have love and tend to have disrespectful characters, do not respect older people and do not respect other students. So this research is to answer and evaluate these problems. The author conducted a qualitative research with a responsive evaluation approach to explore the principles of love found in Romans 12: 9-10 that can be applied by students of the 008 Samarinda Ulu Public Elementary School. This study will explain what are the principles of love for fellow students based on Romans 12: 9-10, then explain how to apply the principles of love to students. Conclusion, the results of this study are expected to help students to understand the principles of love based on the Bible and can be applied in real life.